The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1152/ajpendo.00345.2001
|View full text |Cite
|
Sign up to set email alerts
|

Increased muscle proteolysis after local trauma mainly reflects macrophage-associated lysosomal proteolysis

Abstract: . Increased muscle proteolysis after local trauma mainly reflects macrophage-associated lysosomal proteolysis. Am J Physiol Endocrinol Metab 282: E326-E335, 2002; 10.1152/ajpendo.00345.2001.-Rat gastrocnemius showed increased protein degradation (ϩ75-115%) at 48 h after traumatic injury. Injured muscle showed increased cathepsin B activity (ϩ327%) and mRNA encoding cathepsin B (ϩ670%), cathepsin L (ϩ298%), cathepsin H (ϩ159%), and cathepsin C (ϩ268%). In in situ hybridization, cathepsin B mRNA localized to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 39 publications
3
39
1
3
Order By: Relevance
“…While the initial reaction supports a common stimulus, slight differences seen in the time-dependent process of ligation and degradation activity potentially indicate uncoupled regulation of both systems. Increased ubiquitin mRNA levels seen under wasting conditions [1,12,30] were not observed until 48 h after the locally induced injury [38]. Therefore, it can be speculated that the elevated monomeric ubiquitin we detected 6 h after trauma was caused by accumulation rather than by increased gene expression.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…While the initial reaction supports a common stimulus, slight differences seen in the time-dependent process of ligation and degradation activity potentially indicate uncoupled regulation of both systems. Increased ubiquitin mRNA levels seen under wasting conditions [1,12,30] were not observed until 48 h after the locally induced injury [38]. Therefore, it can be speculated that the elevated monomeric ubiquitin we detected 6 h after trauma was caused by accumulation rather than by increased gene expression.…”
Section: Discussionmentioning
confidence: 74%
“…Results revealed-in line with the present work-reduced ubiquitination activity after injury, but also proteasome activation. These controversial Studies of post-trauma ultrastructural events [33,34], changes in microcirculation [20,24,35], and metabolic effects of surgical trauma [36,37] are supplemented only by the work of Farges et al [38]. The results of this research supporting a lysosomal, UPP-independent protein breakdown by inflammatory infiltrated cells revealed a mechanism that was different from systemically induced muscle wasting.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, we report a new example of a condition under which cathepsin B/L enzyme activities are dramatically altered (22-fold increase) in skeletal muscle. A recent report (20) indicated that inflammatory cells expressed mainly lysosomal enzymes in response to local trauma. In agreement with that study, our histochemical analysis of lysosomal activity (acid phosphatase staining) showed that inflammatory cells were stained positively, whereas desmin-negative fibers did not react with the dye.…”
Section: Discussionmentioning
confidence: 99%
“…Myogenic cells (degenerating myofibers, myoblasts, regenerating myofibers, and growing mature myofibers) and nonmyogenic cells (inflammatory cells) are involved in the different stages of skeletal muscle regeneration and may thus participate in the expression of proteinases (17,20,49). In the present study, an immunohistochemical analysis was first performed to assess the relative proportion of myogenic and nonmyogenic cells over the course of muscle regeneration.…”
mentioning
confidence: 99%